The development of L2 collocational familiarity and its relationship with collocational frequency and congruency - Lou, Jie (Frontiers in Psychology, 2024)
The present study took L2 English learners of different levels in China as subjects to investigate the relationship between collocational familiarity and collocational frequency as well as L1-L2 congruency, and then explored the development of the above relationship as L2 proficiency develops. The results showed that: a moderate positive correlation existed between familiarity and frequency, and the correlation increased with proficiency; a moderate positive correlation also existed between familiarity and congruency, but the correlation decreased with proficiency. Based on previous studies and the present findings, the research group infer that: low familiarity collocations tend to be represented and processed in analytic way and same-translation effect helps accelerate the semantic access of congruent collocations in this process; with the increase in learners’ proficiency, collocation familiarity develops from low to high with frequency effect; high familiarity collocations tend to be represented and processed in holistic way to have direct semantic access; furthermore, learners of two levels have two kinds of collocational representation and semantic access, but low-level learners show more analytic representation and indirect semantic access because of having more low familiarity collocations in the mental lexicon.